2017
DOI: 10.3390/su9050818
|View full text |Cite
|
Sign up to set email alerts
|

Rural Tourism: Development, Management and Sustainability in Rural Establishments

Abstract: Tourism is one of the economic driving forces of Spain: the consolidation of existing tourist destinations and new market niches encourage an upward trend of tourism. The economic impacts produced by tourism are one of the major concerns of the authorities; the question is whether it is possible to continue growing without compromising our environment. This work attempts to answer this issue by analysing one of the tourism segments with higher growth in recent years: rural tourism. Using a model of partial lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 29 publications
(28 reference statements)
2
56
0
Order By: Relevance
“…The destinations able to obtain better profits because of their consolidation do not enjoy the annual stability needed to provide stable income and employment throughout the year. The results are consistent with previous studies where the rural tourism's high seasonality is noted [119]. This fact might condition the support that the tourism industry receives from the citizens, since said support is based on the assessment of potential benefits [124].…”
Section: Conclusion and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The destinations able to obtain better profits because of their consolidation do not enjoy the annual stability needed to provide stable income and employment throughout the year. The results are consistent with previous studies where the rural tourism's high seasonality is noted [119]. This fact might condition the support that the tourism industry receives from the citizens, since said support is based on the assessment of potential benefits [124].…”
Section: Conclusion and Discussionsupporting
confidence: 82%
“…Thus, there is no relationship between the maturity of the destination and annual stability in the number of arrivals, which conditions the role of tourism as a tool for development since those destinations that are able to obtain better benefits due to their consolidated status do not possess the necessary annual stability able to offer income and employment in a stable manner throughout the year. This would make necessary to find alternative sources of income complementary to those derived from tourism as set out in other empirical studies [119,120]. However, the consolidation of the destination does contribute to the stability of medium-sized or already in process of growing, which can be considered as a positive element for these destinations since the inter-annual arrivals will gain in stability, making the tourist activity more stable as well.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, tourism is considered as one of the key economic sectors in creating jobs, increasing the receipt of foreign currency, improving the living standards of local people, supporting the growth of other industries [1,2], as well as the renovation process and international integration of Vietnam in the current context [3,4]. Tourism is defined as "the sum of the phenomena and relationships resulting from travel and stay of non-residents" [5].…”
Section: Introductionmentioning
confidence: 99%
“…Tourism is defined as "the sum of the phenomena and relationships resulting from travel and stay of non-residents" [5]. It is highly appreciated with the name of "smokeless industry" and prioritized as a crucial economic driving force [2]; and it is also called the "green economy" [6]. Everett and Aitchison [7] and Demirović et al [8] found a strong relationship between tourism and the local life, culture and heritage, while Petrović et al [9] discovered that tourism is closely related to natural attractions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, according to the triple bottom line proposed by Elkington [19], sustainability is usually decomposed into three interdependent dimensions (economic, social, and environmental) that, by interacting with each other, are able to determine livable, fair, and feasible development conditions. Moreover, the concepts of sustainability and sustainable development have been particularly applied in tourism, with the consequent birth of the concept of sustainable tourism and the need to establish a lasting balance between resource consumption and economic growth (e.g., [23,31,44,[70][71][72][73][74][75][76][77] Thus, full realization of the sustainability objective can be achieved only by taking into account all three sustainability dimensions. However, academic studies have addressed only one of these dimensions, generating the lack of a holistic and systemic view of the phenomenon [83].…”
Section: The Relationship Between Sustainability Co-evolution and Vmentioning
confidence: 99%